The sub-mm variability of IRC+10216 and o Ceti. Issue 3 (22nd August 2019) - Dharmawardena, Thavisha E; Kemper, Francisca; Wouterloot, Jan G A; Scicluna, Peter; Marshall, Jonathan P; Wallström, Sofia H J
Abstract: We present the sub-mm variability of two of the most well-studied AGB stars, IRC + 10216 and o Ceti. The data are obtained at 450 and 850 μ m as part of pointing calibration observations for the James Clerk Maxwell Telescope's SCUBA-2 instrument over a span of 7 yr. The periods are derived using non-parametric methods, Gatspy Supersmoother and P4J, in order not to assume an underlying shape to the periodicity. These were compared to two Lomb–Scargle parametric methods. We find that for both sources and wavelengths the periods derived from all methods are consistent within 1σ. The 850 μ m phase folded light curves of IRC + 10216 show a time lag of ∼540 d compared to its optical counterpart. We explore the origins of the sub-mm variability and the phase lag using radiative transfer models. Combining the modelling with findings in the literature, we find that the sub-mm emission and phase lag can be partially attributed to the dust formation or destruction cycle. A second, unknown mechanism must be invoked; we defer an investigation of the origin and nature of this mechanism to a future work.